TINDAK TUTUR DIREKTIF DOSEN DENGAN TENAGA ADMINISTRASI: ANCANGAN SOSIOPRAGMATIK BERPERSPEKTIF JENDER (Lingua, 2011)
Problems studied were how the realization of the election code TTD conducted by lecturers and administrative staff within the Faculty of Languages and Arts, State University of Semarang, both men and women against partners and why he said so? And ii) how the realization of politeness TTD conducted by lecturers and administrative staff in the Faculty of Languages and Arts, State University of Semarang, both men and women against partners and why he said so? Method of providing data used is the method of conversation with the basic technique of tapping techniques, and advanced techniques refer to techniques involved in the form of conversation, namely listening and participating in discussions and technical note. The methods of data analysis are a method of frontier, sub-method socio-pragmatic with descriptive-analytic-interpretive techniques. Method of presentation is informal methods and the implementation of such informal methods it is also the use of informal techniques. The results of this study is firstly, in general, the realization of the use of TTD code, either by the dean / assistant dean (male and female), head of the administrative faculty, head subsections, lecturer (male and female), as well as administration staff (male and female) be a code (language) Indonesia, either formal or not formal, and a small portion of mixed code (Indonesian, French, English, Java, and also a non-standard sentence structure.) Secondly, the TTD is one direction, namely from superiors to subordinates, from the senior to junior, from the old to the young. Thirdly, speaking in terms of politeness, dean / assistant dean of men in the rule tends to use direct speech acts, politeness marked either please or not. This case also occurs in administrative staffs officials. In contrast, assistant dean of women tends to use indirect speech acts. Fourthly, both heads and lecturers subsections women tend to use double TTD expressed directly or indirectly. It thus does not occur in male professors who are more likely had a direct TTD. TTD is a direct manifestation of the violation of the principle of politeness, wisdom sub-maxim, whereas indirect TTD is a manifestation of adherence to the principles of politeness, wisdom sub-maxim. Keywords: directive speech acts, actual use of code, politeness